Self-concept of competence of higher education students learning in virtual environments - Moreira, J. António (2014)
Assuming that academic success is influenced not only by the power of learning but also by the way students perceive themselves, we have relied on national studies concerning self-concept of competence of students. The main issue was to situate the self-concept of competence of university students into new virtual learning environments. We aim validate the instrument for collecting empirical data adapted to virtual learning environments, identify the degree of selfconcept of competence, when learning in such an approach, and estimate whether students perceive themselves as much or more competent than in real environments with face-to-face interaction. This research involved 280 higher education students in Social Sciences, who appraised perception and self-concept of competence. The main findings indicate favorable self-concept of competence. Also, the results suggest that the application of online pedagogical models may have a very positive impact on self-concept of competence of students in higher education, even in social dimensions and in the perception of a careful coaching.